Therapeutic approaches in the treatment of keloids: a review - Lima, Igor Mendes; Egypto, Lívio e Vasconcelos do; Sousa, Milena Nunes Alves de (Brazilian Journal of Production Engineering, 2022)
The Keloids are fibrous skin hyperplasia’s, considered benign connective tissue tumors and do not have spontaneous resolution. It can arise spontaneously or secondary to trauma, infection and burns, can affect any part of the body and remain for years after the initial injury. These scars, as they are often aesthetically disfiguring, can cause emotional distress, deterioration in mental health, contribute to a negative body image, difficult relationships and depressive symptoms. Therefore, the objective was to verify therapeutic approaches for the treatment of keloids. An integrative literature review was carried out based on the research question “What are the therapeutic approaches for the treatment of keloids?”. To select the articles that make up this study, searches were performed in the following databases: National Library of Medicine and Science Direct, using as eligibility criteria only studies that addressed the research question, published in the time frame from 2013 to 2021, articles, randomized controlled trials and systematic review articles. The final sample consisted of 12 publications. The results showed that the intralesional injection of corticosteroids was the most used strategy for the treatment of these scars, this is because they have an anti-inflammatory and immunosuppressive effect. Furthermore, surgical excision, cryotherapy, radiotherapy and laser therapy are also currently widely used treatments. There was no definitive and appropriate treatment, however, there are several promising therapies that have shown good results as a combination of surgical and conservative treatments.
Keywords: Keloid; Therapeutics